A generalized thermodynamic theory of the multicaloric effect in single-phase solids. (1st December 2016) - Starkov, Ivan A.; Starkov, Alexander S.
Abstract: The paper presents a generalized thermodynamic theory of the multicaloric effect ( μ CE) in single-phase solids. It is demonstrated that μ CE consists of three well-known effects (electro-, magneto-, and elastocaloric) and three rather new ones that exist due to the interaction between the different fields. They are magnetoelectro-, piezoelectro-, and piezomagnetocaloric effects. Because of a coupling of six effects, it is difficult to identify a single effect in nonlinear materials. Therefore, the linear case is discussed first. Additionally, it is pointed out the necessity to take into account the influence of the gradients of thermodynamic variables on μ CE. Such a focus has enabled us to predict the existence of a flexocaloric effect, that is a change of temperature or entropy with changing deformation gradient. The model is illustrated with data on BST, BaTiO3, PZT ceramics, and In2 NiMnO6 multiferroic.